Recap of Media Democracy Days 2015: Taking on the Federal Election - Ackerley, Christine; Ball, Sydney (Stream: Interdisciplinary Journal of Communication, 2015)
Over the 15 years since its inception Media Democracy Days (MDD) has provided a chance for the public to gather with members of Canadian independent media, journalists, and activists to discuss alternative media and the future of Canadian journalism. This year the MDD community came together with the goal of sharing what has been learned about alternative media practices in light of the recent federal election. MDD took place on November 7th at the Vancouver Public Library and was held in partnership with the SFU School of Communication, OpenMedia, Vancouver Public Library, and Fonds Graham Spry Fund.